New dammarane-type triterpenoid saponins from Panax notoginseng saponins - Li, Qian (J Ginseng Res, 2020)
BACKGROUND: Panax notoginseng saponin (PNS) is the extraction from the roots and rhizomes of Panaxnotoginseng (Burk.) F. H. Chen. PNS is the main bioactive component of Xuesaitong, Xueshuantong, and other Chinese patent medicines, which are all bestselling prescriptions in China to treat cardiocerebrovascular diseases. Notoginsenoside R(1) and ginsenoside Rg(1), Rd, Re, and Rb(1) are the principal effective constituents of PNS, but a systematic research on the rare saponin compositions has not been conducted. OBJECTIVE: The objective of this study was to conduct a systematic chemical study on PNS and establish the HPLC fingerprint of PNS to provide scientific evidence in quality control. In addition, the cytotoxicity of the new compounds was tested. METHODS: Pure saponins from PNS were isolated by means of many chromatographic methods, and their structures were determined by extensive analyses of NMR and HR-ESI-MS studies. The fingerprint was established by HPLC-UV method. The cytotoxicity of the compounds was tested by 3-(4,5-dimethylthiazol-2-yl)-2,5 -diphenyltetrazolium bromide assay. RESULTS AND CONCLUSION: Three new triterpenoid saponins (1–3) together with 25 known rare saponins (4–28) were isolated from PNS, except for the five main compounds (notoginsenoside R(1) and ginsenoside Rg(1), Rd, Re, and Rb(1)). In addition, the HPLC fingerprint of PNS was established, and the peaks of the isolated compounds were marked. The study of chemical constituents and fingerprint was useful for the quality control of PNS. The study on antitumor activities showed that new Compound 2 exhibited significant inhibitory activity against the tested cell lines.